QUALITY OF HIGHER EDUCATION IN EMERGENCY SITUATIONS: EDUCATIONAL LOSSES AND DYSFUNCTIONS OF DIGITALIZATION IN HIGHER EDUCATION AND DISTANCE LEARNING - Marchuk, Аlla (Socio-economic relations in the digital society, 2023)
The article highlights and analyses primary educational losses and key dysfunctions of digitalization in higher education and distance learning in emergencies. The article analyses academic studies by Ukrainian and foreign scientists on the problem of distance learning and the digitalization of education. The main educational losses and dysfunctions of digitalization in higher education are systematized, and factors affecting the quality of higher education during distance learning are determined. The analysis of today’s academic views on positive and negative manifestations of digitalization in higher education made it possible to identify specific dysfunctions related to motivation, control of educational results, communication, and socialization processes. The study is due to the emergencies and difficult circumstances in Ukraine, which significantly affect the organization and the quality of the educational process, and change the landscape of digital technologies and approaches to their implementation in higher education. The article reveals the opportunities and risks associated with digitalization in higher education and distance learning. Distance education caused losses in study time, limited access to the educational process, and changes in educational procedures and academic achievements. The digitalization of higher education resulted in the transformation of the roles of a teacher and a student, influenced the motivation and behaviour of the students and their cognitive processes, and caused particular dysfunctions and educational losses.
Keywords: education digitalization; distance learning; online teaching; educational losses; dysfunctions of education digitalization